IMMUNOHISTOCHEMICAL EXPRESSION OF Ki-67 IN OVARIAN TUMORS & CORRELATION WITH CLINICOPATHOLOGICAL FACTORS - LAVANYA RAJAGOPAL; RAMESH.S (International Journal of Pharma and Bio Sciences, 2016)
Ovarian cancer is the leading cause of death from gynecological malignancies. The prognosis is poor, with an overall survival rate of about 40% in 5 years. Important prognostic factors include stage, age, histological type and grade, ploidity etc. Furthermore, high proliferative activity in the ovarian tumor has been shown to imply a poor prognosis.. The rate at which a tumor proliferates has long been considered to bear a relationship with its clinical course. Immunohistochemical detection of proliferating cells using Ki67 can be used to determine the proliferative potential of a tumor. Ki-67/MIB-1 expression was positively correlated with mitotic count, tumor grade , and stage of disease. We evaluated Ki 67 expression in 42 selected ovarian epithelial tumors which include 14 benign cystadenoma (7 serous, 7 mucinous), 14 borderline cystadenomas (7 serous,7 mucinous), 14 carcinoma (7 serous, 7 mucinous ). Mean Ki 67index of benign, borderline and malignant tumors were 2.9% , 7.2% and 29.9% respectively . A statistically significant difference (p =<0.001) was obtained between these mean Ki 67 indices. Ki 67 immunostaining provides robust prognostic information in ovarian cancers. This biomarker is very much useful to identify borderline tumors which are likely to behave in a malignant fashion and may define subgroups of patients who would be more likely to benefit from cell- cycle dependent chemotherapy regimens, and may guide the development of future therapeutic strategies.